(-)-cis-Carveol, a Natural Compound, Improves β-Amyloid-Peptide 1-42-Induced Memory Impairment and Oxidative Stress in the Rat Hippocampus. (24th April 2020) - Hritcu, Lucian; Boiangiu, Razvan Stefan; de Morais, Mayara Castro; de Sousa, Damião Pergentino
Abstract : Alzheimer's disease (AD) could be considered a multifactorial neurodegenerative disorder characterized by the accumulation of the β -amyloid-peptide (A β ) within the brain leading to cognitive deficits, oxidative stress, and neuroinflammation. The present work was carried out to investigate the neuroprotective effect of (-)- cis -carveol (1% and 3%, for 21 days) against the β -amyloid-peptide 1-42- (A β 1-42-) induced AD. Twenty-five rats were divided into five groups (n = 5 /group): the first group—control (sham-operated); the second group—A β 1-42 (1 mM) that received donepezil treatment (5 mg/kg, as the positive reference drug in the Y-maze and the radial arm maze tests); the third group—A β 1-42 (1 mM); the fourth and fifth groups—A β 1-42 (1 mM) that received (-)- cis -carveol treatment groups (1% and 3%). The results of this study demonstrated that (-)- cis -carveol improved A β 1-42-induced memory deficits examined by using Y-maze and radial arm maze in vivo tests. Also, the biochemical analyses of the hippocampus homogenates showed that (-)- cis -carveol reduced hippocampal oxidative stress caused by A β 1-42. Our results suggested that the use of (-)- cis -carveol may be suitable for decreasing AD-related symptoms.